A Fourier Series Approach to Modeling Nonlinear Damping Using L1 Regularized Regression - Piao, Yanxi. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Computer Science.; Advisor: Felix Huang.; Committee: Elaine Short, and Jivko Sinapov.; Keywords: Computer science, and Health care management.